Combination of a subcutaneous ICD in a patient with a baroreceptor activation device: Feasibility, safety, and precautions: A Case Report. Issue 12 (12th July 2017) - Kuffer, Liz; Steven, Daniel; Halbach, Marcel; Lüker, Jakob; van den Bruck, Jan‐Hendrik; Sultan, Arian
Abstract: We present a case of a patient with a baroreflex activation therapy (BAT) receiving a subcutaneous implantable cardioverter defibrillator (S‐ICD). We anticipated two possible hazardous interactions between the two devices. Stimulation by the BAT could be adjudicated as noise and result in underdetection of ventricular arrhythmias or it might be misinterpreted as ventricular arrhythmias and lead to inappropriate shocks. Postop ensing occurred, the upper limit of pulse width of the BAT was limited because of noise detection by the S‐ICD, but the upper limit of amplitude was limited by patient's discomfort. In this patient, the combination of a BAT and an S‐ICD was safe.